Voluntary Participation of Rural Women in the Sultanate of Oman During the Pre-Renaissance Era: A Socio-historical Perspective - Saleh , Emad Farouk; Al-Maamari , Wafa Said; Abdelghani , Hosni Ibrahim; Abdrabou , Magdy Mostafa; Hassan , Saudi Mohamed; Helal , Ahmed Thabet; R. Aldaraai , Mohammed (Journal of Posthumanism, 2025)
This study focuses on understanding the nature and reality of voluntary activities conducted by rural Omani women in the past, specifically before 1970, an era known in Omani society as the pre-Renaissance era. The study aimed to gather intangible heritage related to the types of voluntary participation of rural women in Omani society during that time. This research belongs to the descriptive-analytical type, aiming to describe a historical phenomenon, namely the voluntary activities of rural women in the past. To achieve this objective, a combination of descriptive and historical methods was employed, allowing for a precise description of these voluntary activities. The study utilized a specially prepared in-depth interview guide, and based on the nature of the field data, content analysis was used to derive the findings. This approach enabled an understanding of voluntary experiences from the participants’ perspectives, facilitating the documentation of these experiences within their historical, social, and economic context.The study included a sample of 20 elderly rural women over 60 years old at the time of data collection in February 2018. The community attachment model was used to analyze the data, considering it an indicator of the extent to which residents of a particular area share cognitive or emotional bonds with their locale. Communities, even those that lack a developed social life, may exhibit high levels of attachment, which applies to the social dynamics in Omani society before 1970. The results reveal that voluntary work was an integral part of the daily life of rural women, that was increasing in both quantity and quality during social and religious occasions. These voluntary initiatives were both individual and group efforts, taking into account the absence of institutionalized voluntary work at that time. Additionally, the social, cultural, and economic nature of rural life played a significant role in creating specific types of voluntary activities for women in addition to the characteristics of those communities. Ultimately, the findings demonstrate that rural women played a central role in fulfilling many of the economic, social, and moral needs of their communities.